2022
DOI: 10.30743/ll.v6i2.4883
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Esp Textbook for the Students of Fashion Design

Abstract: Evaluation is a crucial step in the process of enhancing the quality of educational materials through the design of new content. The evaluation of textbooks in English Language Teaching can be conducted using a variety of techniques. Adapted from Cunningsworth and Kusel (1991) and Skierso (1991), this study utilized checklist instruments to determine whether or not a textbook is appropriate for use. This study provides an overview of ELT textbook evaluation, with a particular emphasis on the use of a checklist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…This result aligns with those found in the studies conducted by previous researchers (e.g. in cases of teachers' perceptions found in Hasibuan and Fithriani (2022), Khodabandeh and Mombini (2018), Khosiyono and Priyana (2019), Nazim (2021), Orfan et al (2021), andSerasi et al (2021), and in case of students' perceptions as found in the studies by Atigh and Khabbazi (2021), Khodabandeh andMombini (2018), andSerasi et al (2021), who found that the participants were satisfied with most of the criteria used to judge the textbooks. However, in this study, the two groups' means are different in terms of the criterion for the topics of the books.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This result aligns with those found in the studies conducted by previous researchers (e.g. in cases of teachers' perceptions found in Hasibuan and Fithriani (2022), Khodabandeh and Mombini (2018), Khosiyono and Priyana (2019), Nazim (2021), Orfan et al (2021), andSerasi et al (2021), and in case of students' perceptions as found in the studies by Atigh and Khabbazi (2021), Khodabandeh andMombini (2018), andSerasi et al (2021), who found that the participants were satisfied with most of the criteria used to judge the textbooks. However, in this study, the two groups' means are different in terms of the criterion for the topics of the books.…”
Section: Discussionsupporting
confidence: 92%
“…While more listening practice is designed, other skills like reading are not practised enough. This is consistent with the findings of Hasibuan and Fithriani (2022). I thought it was challenging to balance language skills if students' needs were unclear.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation